2019
DOI: 10.18510/hssr.2019.7226
|View full text |Cite
|
Sign up to set email alerts
|

Politeness in Online Communication: Retailer-Client Interaction

Abstract: Purpose of the study: The paper aims to unfold politeness in online communication among retailers and clients and debates some ways where cultural values of communication can be taught and thus re-learned. Methodology: The qualitative approach was adopted where discourse analysis method used to review and analyse the updates and comments from Facebook and WhatsApp of conveniently collected data for this study. Main Findings: The study suggest a deterioration of cultural values in communication is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…While some studies have explored impoliteness in online communication (e.g., Chung & Tang, 2022;Sharif et al, 2019;Ranalan, 2020;Zhang, 2022), no relevant work has been found regarding impolite language directed at a government agency like the Department of Education. This research gap emphasizes the need for linguistic investigation in the new normal pedagogical context.…”
Section: Impoliteness Strategiesmentioning
confidence: 99%
“…While some studies have explored impoliteness in online communication (e.g., Chung & Tang, 2022;Sharif et al, 2019;Ranalan, 2020;Zhang, 2022), no relevant work has been found regarding impolite language directed at a government agency like the Department of Education. This research gap emphasizes the need for linguistic investigation in the new normal pedagogical context.…”
Section: Impoliteness Strategiesmentioning
confidence: 99%